Malaysia’s 2014 unprecedented flood catastrophe: A semiparametric estimation of evacuation decisions - Soon, Jan Jan; Kamaruddin, Roslina; Anuar, Abdul Rahim (2016)
In December 2014, Malaysia experienced its worst unprecedented flood catastrophe.This paper looks at the victims’ evacuation decisions of that flood. This paper is unique because previous papers on Malaysian flood-related disasters are only confined to floods of regular or typical scales.This paper is also unique because it uses a semiparametric estimation approach to obtain the marginal impact of the variables of interest on evacuation decisions.This way, there are less distributional assumptions on the error term, and the estimation results would be more robust. Among some of the important findings from the estimations, we find that: (i) victims who have participated in flood awareness programmes are less likely to evacuate to evacuation centres, (ii) victims who are instructed to evacuate are 5 times likelier to do so, (iii) victims with tertiary education are also less likely to evacuate, (iv) larger households are likelier to evacuate, and (v) the further away victims’ homes are from the evacuation centres the likelier they are to evacuate.These findings, some which may seem counterintuitive, are discussed in the conclusion and policy implication section of the paper.